Interactive augmented reality aided software for physics education using exploratory approach - Tan, Kia Kheng (2023)
Interactive Augmented Reality (AR) is a revolutionary technology that has gain significant interest from a wide range of industries, especially the field of education. This project explores the usage of Augmented Reality (AR) technology to enhance physics education, focusing on improve students' physics learning progress with exploratory approach. The project's objective is to develop and evaluate a software application with physics learning modules aided with Augmented Reality (AR) technology, facilitating learners to obtain knowledge. There are 4 core modules in this application includes theory, quiz, simulation and AR playground. This project was mainly developed by Unity and Vuforia. The adopted methodology of this project is ADDIE model. Both System Usability Scale (SUS) and Post-Study System Usability Questionnaire (PSSUQ) were used as the method for evaluating this application. The result of SUS showed that the application has a high level of usefulness, but there was still potential for development. Meanwhile, the result of PSSUQ showed that this application satisfies most of the respondent’s expectation in terms of information quality and system usefulness, but in term of interaction quality, it meets the mean point and remains room for improvement in this aspect.